Bacterial-Induced Blood Pressure Reduction: Mechanisms for the Treatment of Hypertension via the Gut - Cookson, Tyler Alexander (Frontiers in Cardiovascular Medicine, 2021)
Hypertension is a major risk factor for the development of cardiovascular disease. As more research into the gut microbiome emerges, we are finding increasing evidence to support that these microbes may have significant positive and negative effects on blood pressure and associated disorders. The bacterial-derived metabolites that are produced in the gut are capable of widespread effects to several tissue types and organs in the body. It is clear that the extensive metabolic function that is lost with gut dysbiosis is unlikely to be replenished with a single metabolite or bacterial strain. Instead, combinations of bacteria and concomitant therapies will provide a more well-rounded solution to manage hypertension. The bioactive molecules that are recognized in this review will inform on ideal characteristics of candidate bacteria and provide direction for future research on the gut microbiome in hypertension.